Labidocera copepod abundance affected by ocean acidification - Joy N Smith; Claudio Richter; Katharina Elisabeth Fabricius; Astrid Cornils (PANGAEA, 2017)
Labidocera spp. abundances measured from samples collected in Papua New Guinea at natural carbon dioxide seeps. Abundances are compared between two reefs (Dobu and Upa-Upasina) at control and high-CO2 sites for two expeditions. Data includes abundances from net horizontal tows and emergence traps. Data also includes information on life stages and animal lengths, as well as number of oocytes and gut fullness in adult females.
Supplement to: Smith, JN et al. (2017): Pontellid copepods, Labidocera spp., affected by ocean acidification: A field study at natural CO2 seeps. PLoS ONE, 12(5), e0175663, https://doi.org/10.1371/journal.pone.0175663